(untitled) (International Conference on Computers in Education, 2011)
This paper describes our on-going efforts regarding how combining the potential and affordances of two approaches and systems can be used to provide teachers with the ability to design and enact online learning scenarios that include activities performed in outdoor settings. We describe how different technical features of our systems have been integrated combining web-based solutions and mobile applications. We present a detailed example of a learning scenario that was implemented with undergraduate students and included outdoor activities performed via mobile phones, as well as other learning tasks using the web and computers in the classroom and at home. Our results imply of ways teachers and students may use technology in order to support collaborative learning trajectories across different contexts, as well as insights pointing to the pedagogical and design challenges involved in combining a variety of technologies to support outdoors and indoors learning activities.